The whitetail - Ahlstrom, Mark E.; Schroeder, Howard (Mankato, Minn. : Crestwood House, 1983)
Discusses the physical characteristics, habits, behavior, and distribution of the white-tailed deer.
card
Keywords: White-tailed deer -- Juvenile literature; White-tailed deer; Deer